The Strength of Ti-6AL-4V Investigated Using Micro-Pillars - Rayan B. M. Ameen; Dilveen W. Mohammed; Yu-Lung Chiu; Ian P. Jones (Micromachines)
Focused Ion Beam (FIB) has been used to create single α-β colony micro-pillars from a polycrystalline commercial Ti-6Al-4V (Ti-64) sample. Each pillar was selected to have either a single alpha phase, a single beta phase, or two α lamella separated by a thin β phase filet. Then, utilizing a diamond flat tip as a compression platen, uniaxial micro-compression tests were performed on the single crystal α and β pillars as well as a tri-crystal α/β/α pillar using a nano-indenter. Then, utilizing a diamond flat tip as a compression platen, uniaxial micro-compression tests were performed on the single crystal alpha and beta pillars as well as a tri-crystal α/β/α pillar using a nano-indenter. Through the use of Electron Back Scattering Diffraction (EBSD) to choose the crystal orientation along the micro-pillar, three distinct unique slip systems have been selectively triggered by maximizing the Schmid factor for each system. The potential to localize a single crystal volume that can be characterized after deformation is one benefit of the micro-compression approach over traditional mechanical testing. The sample strengths compare well with published data. The mechanical properties of the α-β colonies and the single α and β phases have been compared in order to elucidate the role of the α/β interfaces in determining the critical resolved shear stress.